Transformação digital no setor público: a legislação e os desafios em uma instituição de ensino superior - Grande, Simone Regassone (2025)
This dissertation analyzed the digital transformation (DT) process at the Federal University of São Carlos (UFSCar), relating it to the goals and guidelines of Brazil’s Digital Government Strategy (EGD), established by Decree No. 10.332/2020 and Law No. 14.129/2021. The main objective was to investigate how national digital government guidelines have been appropriated and operationalized in the university’s daily management, considering local specificities such as technological infrastructure, human capacities and regional context. For this purpose, the Digital Transformation Plan (PTD), the Information and Communication Technology Master Plan (PDTIC), Management Reports (2018–2024) and minutes of the Digital Governance Committee (CGD) were analyzed. A qualitative approach was adopted, based on documentary analysis and critical interpretation supported by literature on digital government, public administration and digital transformation. The results reveal advances in process digitalization, systems integration and digital services, but also highlight persistent structural challenges such as limited technical staff, budget constraints, fragmented systems and governance gaps. It is concluded that TD at UFSCar is not consolidated solely by virtue of regulations, but requires coordination between technology, financial investment, processes, organizational culture and people management. The study confirms that technology is necessary but not sufficient to generate sustainable public value, and points to ways to strengthen the role of Federal Universities in building an inclusive, secure and transparent digital government.